Researching in Trans Key: Recommendations for Research with Trans people - Moncayo Quevedo, Jorge Eduardo; Pérez Arizabaleta, María Del Mar (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Research and academic production related to various topics that involve people with transgender life experiences have experienced a significant increase in recent decades. However, in the approach to the Trans population in research processes, some tensions between researchers and participants can be evident. These tensions are particularly manifested in the objectives set and the results obtained, often influenced by the heterocisnormative context in which the researchers operate. In this sense, it is essential to initiate an academic and scientific dialogue that addresses the question of how to carry out research from a transgender perspective, what in this article is called research in a trans key, that is, focused on action without harm, Sensitivity and social responsibility in the investigative approach to Trans people. The objective of this article is to offer recommendations on the development of trans research, in order to avoid possible ethical misconduct in the development of research projects. In total, eleven recommendations are presented that are divided into three specific stages of the research process: outreach to participants, field work and information analysis.